Short- and Long-Term Straw Mulching and Subsoiling Affect Soil Water, Photosynthesis, and Water Use of Wheat and Maize - Yang, Yonghui; Wu, Jicheng; Du, Yan-Lei; Gao, Cuimin; Pan, Xiaoying; Tang, Darrell W. S.; van der Ploeg, Martine (Frontiers in Agronomy, 2021)
Water shortages and rainfall variability lead to a decrease in grain yield. Straw mulching (SM), subsoiling (S), and combined amendments (subsoiling + straw mulching, SS) are potential solutions for maintaining crop productivity and water resource sustainability. However, short- and long-term applications of these methods appear to result in different yield and water use efficiency outcomes. In this study, we, therefore, compared short- and long-term applications of SM, S, and SS, with a control. We analyzed field experimental data of wheat and maize cultivation with control (conventional tillage), SM, S, and SS treatments to assess the impact on yield and water use efficiency, resulting from short- and long-term applications of these practices. The results show that SS treatment led to higher soil water storage (SWS) compared with other treatments during the regreening, jointing, and booting stages of wheat, and the big bellmouth and filling stages of maize in the short- and long-term experiments. However, long-term SS treatment also led to higher SWS in the growth stage of wheat in 2015–2016 and in the growth stage of maize in 2015. Additionally, SS treatment was conducive to raising the net photosynthetic rate (Pn) and leaf water use efficiency (LWUE) of wheat compared with other treatments in 2015 and 2016. Conversely, Pn and LWUE of maize under S and SS treatments were higher (P < 0.05) compared with other treatments in the two studied years. Short-term treatment led to higher wheat yield compared with long term in 2014–2015 (ample rainfall) and of maize in 2016 (low rainfall). The yield of wheat under long-term S treatment in 2015 was 9625.-kg hm−2, which was the highest (P < 0.05) in 2 years, with a 17.7% increase compared with the control, followed by short-term S treatment. However, the water use efficiency (WUE) of wheat under long-term SS treatment in 2016 was the highest (P < 0.05) compared with other treatments. The yield of maize under SM and S treatments was higher than other treatments, whereas the WUE of maize under long-term SS treatment in 2016 was still the highest (P < 0.05). Our findings provide evidence that S and SS treatments improve both crop productivity and water resource sustainability, and long-term application resulted in higher productivity than short-term application.